Self-Care and Self-Management Among Adolescent T2DM Patients: A Review - Eva, Jafrin Jahan; Kassab, Yaman Walid; Neoh, Chin Fen; Ming, Long Chiau; Wong, Yuet Yen; Abdul Hameed, Mohammed; Hong, Yet Hoi; Sarker, Md Moklesur Rahman (Frontiers in Endocrinology, 2018)
Uncontrolled hyperglycaemia can lead to macro and microvascular complications. Adolescents with T2DM develop similar complications seen in adults with diabetes, including cardiovascular disease, stroke, myocardial infarction, renal insufficiency and chronic renal failure. Although regular medical follow up is essential in averting long-term complications, patients with diabetes mellitus need to perform holistic self-care activities such as opting for a healthy diet, physical activity, self-monitoring and medication taking, outside of the clinical settings. To the best of our knowledge, only a limited number of studies have focused on the self-care activities and self-management, including self-care practices, supportive network, self-care education program and some of the studies concentrated on the appreciation of self-care in the adolescent with T2DM. This review aimed to analyse self-care and self-management among adolescents with T2DM and discuss the impact of self-care and self-management on glycaemic control and, hence, to reduce the diabetes-related complications. The difficulties faced by adolescents in self-managing their disease are also highlighted. Such information is essential for healthcare providers in promoting self-care practices among diabetic adolescents. To retrieve the articles, a thorough search through the literature was performed using the three databases of Medline, Google Scholar, and Scopus. In this review, we included the articles that focused on the self-care and self-management of adolescent T2DM patients aged between 12-19 years. Findings from this review suggest that healthy food adaptation, adequate physical activity, proper medication practices and regular glucose monitoring are the most common self-care practices. Parental involvement and clinician’s responsibility also contribute towards the advancement of the self-care and self-management of adolescent diabetes. Fruitful changes to independent, self-management regimens and supportive network for appropriate administration are vital factors to enhance clinical outcomes of the adolescent with T2DM.